Performance of Auto Glass Powder-High Calcium Fly Ash Geopolymer Mortar Exposed to High Temperature - Zaetang, Yuwadee; Wongkvanklom, Athika; Pangdaeng, Saengsuree; Hanjitsuwan, Sakonwan; Wongsa, Ampol; Sata, Vanchai; Chindaprasirt, Prinya (Civil Engineering Journal, 2025)
Waste glass enhances concrete sustainability by reducing virgin material use and recycling waste. In traditional concrete, it boosts strength through pozzolanic reactions, while in geopolymer concrete, it improves durability, insulation, and resistance to harsh conditions. This study investigated the viability of substituting auto glass powder (AGP) for high-calcium fly ash (FA) in geopolymer mortar formulations. AGP was utilized as a substitute for high-calcium FA at substitution levels ranging from 0% to 40% by weight. The study examined the physical properties, compressive strength, thermal insulation, and high-temperature performance of the geopolymer composites. The findings indicated that a higher AGP content corresponded with a reduced mortar flow, while increasing the proportion of AGP resulted in the diminished compressive strength of the geopolymer composites. Incorporating 10–20% AGP into the geopolymer mortar gave satisfactory compressive strengths (75–85%) compared to the reference mortar. Thermal conductivity testing indicated that AGP enhanced the thermal insulating properties of mortar. Notably, the compressive strength, after being exposed to 600–900°C, improved with the inclusion of the AGP. Based on XRD, the combeite crystalline phase was present in the mortars containing 20% and 40% AGP after being subjected to 900ºC. This phase contributed to the durability and stability of the material. Thus, it was confirmed that AGP not only served as a beneficial additive but also could play a crucial role in the thermal resilience of geopolymer systems.